Effects of breed and genomic inbreeding on milk, fat and protein lactation yields and fertility traits in pasture-based dairy cows in Argentina - Beribe, Maria Jose; Carignano, Hugo Adrian; Poli, Mario Andres; Lopez-Villalobos, Nicolás (Cambridge University Press, 2024)
The objective of the current study was to evaluate the effects of breed and genomic inbreeding on 305-day lactation yields of milk, fat and protein; and fertility traits of pasture-based dairy cows in Argentina. The genomic inbreeding and heterozygosity of 890 first-lactation cows and 27 bulls were calculated through methods based on the genomic relationship matrix and run of homozygosity using 44 174 single-nucleotide polymorphisms. Cows were classified into four breed groups: Holstein, Holstein crossbred, Holstein–Jersey crossbred and Jersey crossbred. The effect of genomic inbreeding was not significant on production traits, but inbred cows increased 3.0 days calving to conception interval (CCI) per 1% genomic inbreeding. On average, purebred Holstein cows produced 1119 kg milk, 22 kg fat and 30 kg protein more than Jersey crossbred cows. In the case of the fertility traits, Jersey crossbred cows had 45 days shorter CCI than purebred Holstein cows. A possible reason for the non-significant effects of genomic inbreeding of production and fertility traits is that these effects were evaluated in a crossbred population in which rates of heterozygosity would operate to some extent in the opposite direction to rates of genomic inbreeding.